Effect of postmenopausal status on insulin sensitivity in myanmar women - Thet, Lwin Aye; Sein, Mya Thanda; Latt, Tint Swe (Asian Journal of Medical Sciences, 2016)
Background: Animal studies show that ovarian hormone deficiency is associated with development of insulin resistance. In women, the menopause transition marks the cessation of ovarian function and insulin sensitivity would be reduced in postmenopausal women. Aim and Objectives: This study aimed to evaluate the insulin sensitivity in Myanmar postmenopausal women compared to premenopausal women Material and Methods: A cross sectional comparative study was undertaken in non obese, normal glucose tolerant post menopausal women (n=42, BMI (mean± SD) 21.3±2.8 kg/m2, age 52.6±4.4 years) and premenopausal women (n=33, BMI(mean± SD) 19.7±2.2 kg/m2, age32.7±4.9 years). Insulin sensitivity was assessed by homeostasis model assessment method of insulin resistance (HOMA-IR) based on fasting blood glucose and fasting serum insulin level. Blood glucose was determined by glucose oxidase method. Serum insulin was estimated by enzyme linked immunosorbent assay (ELISA). Results:No differences in fasting blood glucose level (Mean ±SD 4.87±0.51 vs. 4.76±0.63mmol/L), fasting serum insulin level [median and interquartile range (IQR) 8.1 (6.7-11.8) vs. 8.1(6.5-9.9) µ IU/ml] and HOMA-IR [median and IQR 1.7 (1.4-2.8) vs. 1.7 (1.2-2.2)] were found between premenopausal and postmenopausal women. Conclusion: Postmenopausal status has no effect on insulin sensitivity in postmenopausal women. Asian Journal of Medical Sciences Vol.7(5) 2016 36-41